2021
DOI: 10.24193/jrhe.2021.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Dilemma of Unrelenting Workload Amidst Covid-19 Pandemic: An Agenda for University Female Academics

Abstract: The dynamic changes in the South African higher education environment have seen academics immersed in increasing workloads to keep up with the university mandate. The outbreak of the Covid-19 pandemic has raised significant challenges for the higher education community and intensified complications related to workload and in particular for female academics. The understanding of the management of workload is pertinent, and therefore the article examines the components of workload and implications of the Covid-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Previous studies concluded that females in HE suffered an increased workload and that managing work–life balance was challenging compared to males (Obianuju and Gamede, 2021; Garraio et al. , 2022; Newlin and Anthony, 2022).…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies concluded that females in HE suffered an increased workload and that managing work–life balance was challenging compared to males (Obianuju and Gamede, 2021; Garraio et al. , 2022; Newlin and Anthony, 2022).…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…, 2021; Romeo et al. , 2021; Obianuju and Gamede, 2021; Garraio et al. , 2022; Newlin and Anthony, 2022).…”
Section: Literature Review – Insights and Gapsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many contributing causes to academic burnout including unmanageable workload obligations (Cadez et al. , 2017) and extenuating external factors (Okeke-Uzodike and Gamede, 2021). As in other settings, burnout has been exacerbated by the pandemic (Wong et al.…”
Section: Introductionmentioning
confidence: 99%